2006
DOI: 10.2459/01.jcm.0000215277.62767.8f
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of cardiac tamponade

Abstract: A case of a 67-year-old woman with cardiac tamponade caused by toothpick ingestion is presented. At clinical presentation, it mimicked postinfarction ventricular free wall rupture and the diagnosis was not made until the operation. Ingested toothpicks have often been reported as a cause of intestinal injuries, but in this rare case the toothpick migrated into the pericardium and caused laceration of the right coronary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Li et al showed a very high overall mortality rate after toothpick ingestion (18%) (2). In one case report, the ingested toothpick migrated out of the gastrointestinal tract into the pericardium, causing cardiac tamponade (3). A case has recently been reported in which a toothpick migrated from the gastric wall to the pericardium, injuring the right coronary artery, requiring coronary artery bypass grafting (4).…”
Section: Discussionmentioning
confidence: 97%
“…Li et al showed a very high overall mortality rate after toothpick ingestion (18%) (2). In one case report, the ingested toothpick migrated out of the gastrointestinal tract into the pericardium, causing cardiac tamponade (3). A case has recently been reported in which a toothpick migrated from the gastric wall to the pericardium, injuring the right coronary artery, requiring coronary artery bypass grafting (4).…”
Section: Discussionmentioning
confidence: 97%
“…Swallowed foreign bodies tend to get stock in the upper and lower esophageal sphincter in the esophagus. 2 …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for toothpick ingestion include alcohol intoxication, dulled palatal sensation most commonly due to the presence of dentures, rapid ingestion of food, habitual chewing of toothpicks, and mental retardation 3,6,7. The most common sites of injury are the duodenum and sigmoid colon5 although toothpicks have been reported to migrate and cause injury to the retroperitoneum causing upper urinary tract obstruction,8 pericardium causing injury to the right coronary artery,9 and cardiac tamponade 10. Unusual presentations include liver abscess,11,12 subcutaneous emphysema of leg,13 and arterial-enteric fistula 14…”
Section: Discussionmentioning
confidence: 99%